Assessment of effect of international finance facility for the development of rural infrastructure and community service: a case of Millennium Development Authority in the Ejura-Sekyedumase Municipality in Ashanti Region - Akowuah, Theresah (2016)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of Science in Development Policy and Planning.